Physicochemical Properties and Microbial Inhibition on Biofilms Cassava Starch with Green Cayenne Pepper Leaf Extract (Capsicum Frutescens L) - Rahmadhia, Safinta Nurindra (Jurnal Keteknikan Pertanian, 2023)
Biofilm is an alternative packaging for food products in the form of thin layers made from natural materials that are safe to use and for consumption. One of the materials used in the manufacture of biofilms is starch. However, starch-based biofilms have a weakness, namely their low water resistance. The addition of green cayenne pepper leaf extract is thought to improve the physicochemical properties as well as the potential to become antimicrobial for biofilms. The purpose of this study was to determine the effect of the addition of green cayenne leaf extract on the physicochemical and antimicrobial properties of cassava starch biofilm. The green cayenne leaf extract formulations used in this study were F0 (control), F1 (1 ml), F2 (1.5 ml), F3 (2 ml), F4 (2.5 ml) and F5 (3 ml) with 3 repetitions each. The results of this study indicate that the addition of green cayenne leaf extract has a significant effect on thickness (0.17-0.26 mm), tensile strength (2.25-5.87 Mpa), elongation (44.9-81.9 % ), solubility (23.1-27.6 %), water vapor permeability (5.20-9.23 g/m.s.kPa), moisture content (11.3-11.8 %) and microbial inhibition on F5 results in higher values ​​of F0 and F1.